Step washing: A modified pretreatment approach for industrial applications to improve chemical composition of agricultural residues. (December 2021) - Singhal, Abhishek; Goossens, Maria; Fantozzi, Davide; Raiko, Antti; Konttinen, Jukka; Joronen, Tero
Highlights: A novel pretreatment approach was tested to improve fuel composition of biomass. Lab- and pilot-scale testing was done for the novel washing pretreatment. Upto 99% Cl, 92% K, 80% S, 72% ash, and 60% N removal was achieved by step-washing. Much lower fouling, slagging and corrosion propensity was found after step-washing. Pressing and high-water temperature further increase washing efficiency by 6–24%. Abstract: To improve the efficiency and applicability of the washing pre-treatment for combustion, pyrolysis and gasification, a modified approach was developed in the present study. Two novel washing approaches were tested using wheat straw and empty fruit bunches of oil palm: multiple-step washing with fresh water (SWFW) and wastewater recirculation (SWWR). SWFW showed the high removal of K (<68%), Cl (<99%), S (<80%), N (<58%), and ash (<52%) reducing fouling, slagging, and corrosion propensity of the biomass. Furthermore, with one-third the amount of water used in SWFW, SWWR showed similar to higher efficiency than SWFW with relatively better energy (98%) yields. Industrial-scale pilot testing was also conducted for the validation of the SWWR approach, which showed similar findings as the lab-scale results. The effect of a high washing temperature and pressing on washing efficiency and characterisation of wastewater was also determined. Overall, SWWR with pressing is recommended for industrial applications.